2004
DOI: 10.1016/s0006-3495(04)74170-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Antiinflammatory Drugs with EPC Liposomes: Calorimetric Study in a Broad Concentration Range

Abstract: Isothermal titration calorimetry was used to characterize and quantify the partition of indomethacin and acemetacin between the bulk aqueous phase and the membrane of egg phosphatidylcholine vesicles. Significant electrostatic effects were observed due to binding of the charged drugs to the membrane, which implied the use of the Gouy-Chapman theory to calculate the interfacial concentrations. The binding/partition phenomenon was quantified in terms of the partition coefficient (K(p)), and/or the equilibrium co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…One of the major goals of current research in biophysics is to characterize the fundamental interactions between drugs or macromolecules and multimolecular structures such as lipid monolayers or bilayers (30)(31)(32)(33)(34)(35)(36). Formation of lateral microdomains is particularly important in this respect both from the structural and functional points of view.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major goals of current research in biophysics is to characterize the fundamental interactions between drugs or macromolecules and multimolecular structures such as lipid monolayers or bilayers (30)(31)(32)(33)(34)(35)(36). Formation of lateral microdomains is particularly important in this respect both from the structural and functional points of view.…”
Section: Discussionmentioning
confidence: 99%
“…The former emphasizes the correlation for the detection of the difference between very weak and very strong PLD inducers, and is more strongly affected by single outliers, whereas the latter emphasizes the correlation for the detection of the differences in potency over a wide interval (Figure 11). In linear correlations the EC 50 values of Morelli et al [205] reveal best correlation with PLD index, and c 2 data from Nioi et al [194] and Kasahara et al [192] have their second-best correlation with PLD index. The data reported by Bhandari et al [195] show the best and second-best correlations to the data sets of Kasahara et al [192] and Nioi et al [194] ( Table 2).…”
Section: Comparison Of Screening Methodsmentioning
confidence: 86%
“…In general, the correlation to PLD index is much better for values that reflect the concentrations of drugs required to inflict significant PLD, that is, c 2 and EC 50 . Another similar value is the A 50 value of Bhandari et al, [195] who also used a fluorescent lipid accumulation assay, collected the data using three different cell lines (HepG2 cells, rat hepatocytes, and rhesus monkey hepatocytes), and found significant differences between the cell lines for a few of the drugs.…”
Section: Comparison Of Screening Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetic study has demonstrated that the hydrophobic piroxicam has a slow absorption via oral route, which resulted in low bioavailability of the drug and delayed the onset of its therapeutics effects [7]. Due to the potential modification of drug's bioavailability and therapeutic index using liposomal technology, the strategy to entrap piroxicam in liposomes is therefore deemed important in pharmaceutical field [8,9]. Over the years, numerous techniques and procedures have been described to prepare liposome-encapsulated drugs with different sizes and characteristics.…”
Section: Introductionmentioning
confidence: 99%